The Land Question (Un)Resolved: An Essay Review (Historia, 2021)
Despite bold claims by Zanu(PF) and President Mugabe that the land question has been resolved in Zimbabwe, thanks to the controversial fast-track land-reform programme initiated in 2000, its contested authority and emotive capacity continue to play an influential role in Zimbabwean politics. This is evidenced by none other than Mugabe himself, who again played the land card in his recent electoral campaigns. With no hint of irony or remorse, Mugabe simultaneously called for the country's new farmers to consolidate the "gains of our land-reform programme", whilst adamantly proclaiming that this summer was going to be the "mother of all agricultural seasons" despite the fact that "there is hunger in the country and a shortage of food". This seemingly contradictory rhetoric was accompanied by a massive vote-buying exercise involving the handing out of millions of dollars worth of agricultural equipment and inputs. As unsurprising as the employment of this tactic by Mugabe was, it shows that land and its troubled history still remains at the forefront of the country's political and social imagination and is far from being a problem of the past. The dramatic and devastating effects of the government's land-reform programme marked a significant shift in land politics up to that point and served to drastically reinvigorate, radicalise and fragment an already highly emotive and politicized debate. This essay review attempts to plot a course through the treacherous labyrinth of literature that has emerged on the land question in Zimbabwe since the start of the land reforms in 2000. By doing so, it hopes to highlight the major debates that have arisen, how analyses and points of focus have changed over time and why there has been an extraordinary loss of "the middle ground" in the ensuing debates.
Keywords: Zanu(PF); President Mugabe; Zimbabwe; land-reform; major debates; middle ground